Conjugation of desgalactotigonin into nanoliposomal particles and measurement of in vitro inhibitory activities on six cancerous cell lines - Thi Phuong, Do; Thi Nga, Nguyen; Thi Cuc, Nguyen; Ha Phuong, Trieu; Hai Yen, Pham Thi; Tuan Anh, Hoang Le; Thi Thao, Do (Vietnam Journal of Biotechnology, 2021)
Cancer is a deadly disease with high mortality and having no efficient drugs for treatment. Therefore, discovering and developing new drugs with improved efficiency, lowering side effects and highly targeting, are obtaining much attention over the world. Desgalactotigonin (DGT) isolated from the plant Lu-lu-duc (Solanum nigrum) presented its promising anticancer activities by inhibiting a category of cancer cell lines. However, the compound also showed the limitation in reality applications since its low solubility as well as highly toxic, same as many other natural compounds. In order to improve DGT bioavailability, the compound was conjugated into nanoliposomes, ideal drug carriers. In this research, DGT was entrapped into nanoliposomal particles with entrapment efficiency (EE) at 70.26% and showed typical bilayer spherical morphology. The conjugation presented average size as 93.17 nm, PDI as 0.168 and zeta voltage as -3.67 mV. The anticancer activities of the DGT-nanoliposomes exhibited with IC50 values ranging from 38.94 - 61.69 µg/mL (equal to DGT amount in the complex as 1.30 - 2.06 µg/mL) on six different cancer cell lines. Typically, the DGT nanoliposomes presented much lower toxicity on HEK-293 normal cell line with the IC50 as 2,75 µg/mL, showing its potential clinical applications.